A phenomenological analysis of the emotional experiences of graduate preservice student teachers in Indonesia [version 3; peer review: 2 approved] - Dyah Sunggingwati; Sunardi Sunardi; Istanti Hermagustiana; Desy Rusmawaty; Famala Eka Sanhadi Rahayu (F1000Research)
Background Addressing preservice teachers' emotions can help them develop the emotional connections necessary for successful teaching practicums and professional learning experiences. To understand preservice teachers’ emotions towards their surroundings, the researchers used an emotional geography framework to map out the source of their negative and positive emotions and how those feelings affect their beliefs, teaching style, and paradigms. Emotional geographies were divided into two categories (i.e., emotional distance and emotional closeness), which were further mapped into five major themes (i.e., sociocultural, moral, professional, physical, and political). This study aims to investigate the emotional geographies of graduate preservice teachers during their teaching practicums in Indonesia by adapting Hargreaves’ (2001) theoretical model, thereby identifying key dimensions and validating the adapted framework. Methods This study examined emotional geographies of 15 graduate preservice student teachers of Teacher Training and Education Faculty of Mulawarman University during their teaching practicums. Moreover, this study used a qualitative design involving semi-structured interviews with 15 graduate students who completed their teaching practicums. Results The participants experienced all emotional geographies (sociocultural, moral, professional, physical, and political) that reshaped their beliefs and teaching styles, especially related to teaching undergraduate students. These emotions are generally experienced when the participants deal with the students and cooperating teachers. Conclusions It was found that teachers needed to be strict when instilling discipline in their students, develop friendships with their students to maintain classroom control, and require comprehensive preparation to create teacher's confidence and answer their students' questions. In effect, the theoretical framework of emotional geography when teaching undergraduates during practicums gave student teachers valuable experience to cope with all common teaching challenges and professional growth.